Transcriptome sequencing of facial adipose tissue reveals alterations in mRNAs of hemifacial microsomia - Bingyang Liu; Wei Liu; Shanbaga Zhao; Lunkun Ma; Tianying Zang; Changjin Huang; Kaiyi Shu; Hengbin Gao; Xiaojun Tang (Frontiers Media S.A., 2023)
Hemifacial microsomia (HFM) is a common congenital malformation of the craniofacial region, including mandibular hypoplasia, microtia, facial palsy and soft tissue deficiencies. However, it remains unclear which specific genes are involved in the pathogenesis of HFM. By identifying differentially expressed genes (DEGs) in deficient facial adipose tissue from HFM patients, we hope to provide a new insight into disease mechanisms from the transcriptome perspective. RNA sequencing (RNA-Seq) was performed with 10 facial adipose tissues from patients of HFM and healthy controls. Differentially expressed genes in HFM were validated by quantitative real-time PCR (qPCR). Functional annotations of the DEGs were analyzed with DESeq2 R package (1.20.0). A total of 1,244 genes were identified as DEGs between HFM patients and matched controls. Bioinformatic analysis predicted that the increased expression of HOXB2 and HAND2 were associated with facial deformity of HFM. Knockdown and overexpression of HOXB2 were achieved with lentiviral vectors. Cell proliferation, migration, and invasion assay was performed with adipose-derived stem cells (ADSC) to confirm the phenotype of HOXB2. We also found that PI3K−Akt signaling pathway and human papillomavirus infection were activated in HFM. In conclusion, we discovered potential genes, pathways and networks in HFM facial adipose tissue, which contributes to a better understanding of the pathogenesis of HFM.